Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine the quotient [tex]\(Q(x)\)[/tex] and the remainder [tex]\(R(x)\)[/tex] when the polynomial [tex]\(P(x) = x^3 - 3x^2 + 4x - 2\)[/tex] is divided by [tex]\(D(x) = x - 2\)[/tex], we can manually perform polynomial long division.
### Step-by-Step Polynomial Division:
1. Setup the Division:
[tex]\[ \text{Divide } x^3 - 3x^2 + 4x - 2 \text{ by } x - 2. \][/tex]
2. First Division:
- Divide the leading term of the dividend [tex]\(x^3\)[/tex] by the leading term of the divisor [tex]\(x\)[/tex]:
[tex]\[ \frac{x^3}{x} = x^2 \][/tex]
- Multiply [tex]\(x^2\)[/tex] by [tex]\(x - 2\)[/tex]:
[tex]\[ x^2 \cdot (x - 2) = x^3 - 2x^2 \][/tex]
- Subtract this result from the original polynomial:
[tex]\[ (x^3 - 3x^2 + 4x - 2) - (x^3 - 2x^2) = -x^2 + 4x - 2 \][/tex]
3. Second Division:
- Divide the leading term of the new dividend [tex]\(-x^2\)[/tex] by the leading term of the divisor [tex]\(x\)[/tex]:
[tex]\[ \frac{-x^2}{x} = -x \][/tex]
- Multiply [tex]\(-x\)[/tex] by [tex]\(x - 2\)[/tex]:
[tex]\[ -x \cdot (x - 2) = -x^2 + 2x \][/tex]
- Subtract this result from the new dividend:
[tex]\[ (-x^2 + 4x - 2) - (-x^2 + 2x) = 2x - 2 \][/tex]
4. Third Division:
- Divide the leading term of the new dividend [tex]\(2x\)[/tex] by the leading term of the divisor [tex]\(x\)[/tex]:
[tex]\[ \frac{2x}{x} = 2 \][/tex]
- Multiply [tex]\(2\)[/tex] by [tex]\(x - 2\)[/tex]:
[tex]\[ 2 \cdot (x - 2) = 2x - 4 \][/tex]
- Subtract this result from the new dividend:
[tex]\[ (2x - 2) - (2x - 4) = -2 + 4 = 2 \][/tex]
Hence, the quotient [tex]\(Q(x)\)[/tex] is:
[tex]\[ Q(x) = x^2 - x + 2 \][/tex]
And the remainder [tex]\(R(x)\)[/tex] is:
[tex]\[ R(x) = 2 \][/tex]
### Verification (Using Substitution or Synthetic Division):
We substitute [tex]\(x = 2\)[/tex] into the original polynomial to verify the remainder:
[tex]\[ P(2) = 2^3 - 3 \cdot 2^2 + 4 \cdot 2 - 2 = 8 - 12 + 8 - 2 = 2 \][/tex]
Thus, the remainder when [tex]\(x = 2\)[/tex] is indeed 2.
### Conclusion:
With the found quotient and remainder, the correct answer is:
b) [tex]\(Q(x) = x^2 - x + 2 \)[/tex] and [tex]\(R(x) = 2\)[/tex]
### Step-by-Step Polynomial Division:
1. Setup the Division:
[tex]\[ \text{Divide } x^3 - 3x^2 + 4x - 2 \text{ by } x - 2. \][/tex]
2. First Division:
- Divide the leading term of the dividend [tex]\(x^3\)[/tex] by the leading term of the divisor [tex]\(x\)[/tex]:
[tex]\[ \frac{x^3}{x} = x^2 \][/tex]
- Multiply [tex]\(x^2\)[/tex] by [tex]\(x - 2\)[/tex]:
[tex]\[ x^2 \cdot (x - 2) = x^3 - 2x^2 \][/tex]
- Subtract this result from the original polynomial:
[tex]\[ (x^3 - 3x^2 + 4x - 2) - (x^3 - 2x^2) = -x^2 + 4x - 2 \][/tex]
3. Second Division:
- Divide the leading term of the new dividend [tex]\(-x^2\)[/tex] by the leading term of the divisor [tex]\(x\)[/tex]:
[tex]\[ \frac{-x^2}{x} = -x \][/tex]
- Multiply [tex]\(-x\)[/tex] by [tex]\(x - 2\)[/tex]:
[tex]\[ -x \cdot (x - 2) = -x^2 + 2x \][/tex]
- Subtract this result from the new dividend:
[tex]\[ (-x^2 + 4x - 2) - (-x^2 + 2x) = 2x - 2 \][/tex]
4. Third Division:
- Divide the leading term of the new dividend [tex]\(2x\)[/tex] by the leading term of the divisor [tex]\(x\)[/tex]:
[tex]\[ \frac{2x}{x} = 2 \][/tex]
- Multiply [tex]\(2\)[/tex] by [tex]\(x - 2\)[/tex]:
[tex]\[ 2 \cdot (x - 2) = 2x - 4 \][/tex]
- Subtract this result from the new dividend:
[tex]\[ (2x - 2) - (2x - 4) = -2 + 4 = 2 \][/tex]
Hence, the quotient [tex]\(Q(x)\)[/tex] is:
[tex]\[ Q(x) = x^2 - x + 2 \][/tex]
And the remainder [tex]\(R(x)\)[/tex] is:
[tex]\[ R(x) = 2 \][/tex]
### Verification (Using Substitution or Synthetic Division):
We substitute [tex]\(x = 2\)[/tex] into the original polynomial to verify the remainder:
[tex]\[ P(2) = 2^3 - 3 \cdot 2^2 + 4 \cdot 2 - 2 = 8 - 12 + 8 - 2 = 2 \][/tex]
Thus, the remainder when [tex]\(x = 2\)[/tex] is indeed 2.
### Conclusion:
With the found quotient and remainder, the correct answer is:
b) [tex]\(Q(x) = x^2 - x + 2 \)[/tex] and [tex]\(R(x) = 2\)[/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.